Analisis Neraca Pembayaran Indonesia Dengan Pendekatan Keynesian dan Monetaris - Effendy, Arif Khusni (Jurnal Ilmiah Mahasiswa FEB, 2014)
ThisÂ  paperÂ  analyzes how in the short term and long term fluctuations in the balance of payments of Indonesia can be explained by Keynesian approach (elasticity and absorption) and Monetary approach. The basic approach used is the monetary approach, using foreign exchange reserves (NFA) as a proxy the balance of payments. But also included in the exchange rate and GDP to study the influence of Keynesian approach to the variables of the balance of payments. Using Error Correction Model (ECM) with two steps, the first step in using the OLS to analyze the effect of long term between balance of payments and its determinants. The second step uses ECM to analyse the influence of short-term. As a result, that the exchange rate has a positive and significant impact on the balance of payments in the short term and long term. The GDP has only positive and significant influence on the balance of payments in the short term. While inflation and interest rates as variables of monetary approach does not significantly affect the balance of payments in the short and the long term.Keyword: Balance of Payment, Keynesian Approach, Monetary Appoach, OLS, and ECM